Analysing EU Countries’ Digital Progress Towards Sustainable Development Goals - Alexandra-Nicoleta Ciucu (Durnoi); Cosmin Alexandru Teodorescu; Vanesa Madalina Vargas; Corina Ioanas (Amfiteatru Economic)
The article analyses the level of digitalization in the European Union (EU) and correlates the results with the Sustainable Development Goals formulated by the United Nations. The paper provides figures on the number of enterprises receiving orders online, the share of enterprises' turnover on e-commerce, the number of employed ICT specialists by sex (female), and the number of individuals using the Internet for interacting with public authorities in order to determine the differences between the member states. The next step carried out in the current article was to conduct a three-year forecast of the indicators listed previously. The methods used to make predictions are Autoregressive Integrated Moving Average (ARIMA) and Double Exponential Smoothing. The results highlight a projected increase in individuals using the Internet for interacting with public authorities, the rise in e-commerce turnover, the expansion of high-speed Internet coverage, and the growth in the percentage of femaleemployed ICT specialists. Furthermore, the originality of this research lies in providing valuable insights into the correlation between digitalization and sustainable development in the European Union. The forecasted trends indicate positive advancements toward multiple Sustainable Development Goals (SDGs). These findings demonstrate the EU's commitment to achieving SDG targets related to effective institutions, public access to information, economic productivity, technology access, quality education, and gender equality. The study emphasises the crucial role of digitalization in driving sustainable development and underscores the progress made by the EU in aligning its efforts with the SDGs